The effect of two different resistance training programs on hemorheological factors in healthy inactive men - فتح الله هاویل; افشار جعفری; سجاد احمدی زاد; سعید دباغ نیکوخصلت (Shahid Beheshti University, 2017)
Aim: Based on controversies about the effects of resistance training on hemorheological parameters associated with cardiovascular disease, this study was carried out to determine the effect of 12 weeks of resistance training (hypertrophy and maximal strength) on hemorheological parameters in healthy inactive men. Methods: Thirty nine collegiate men (18-20 years) were randomly divided into three groups: control (n =12), hypertrophy (n =13) and strength (n =13) training groups. Training groups participated in 12 weeks of resistance training (3 sessions / week, 6 stations / session and 3 times per station). Hypertrophy and maximal strength resistance training were performed at 65-70% and 80-85% of one repetition maximum, respectively. Blood samples were taken before and 48 hours after the training period and were analyzed for measuring the hemorheological variables. Hemorheological data were analyzed by using the independent one-way ANOVA. Results: The significant reductions in total protein, plasma viscosity and aggregation of red blood cells in inactive men were found after 12 weeks of hypertrophy and maximal resistance training (P